Patient satisfaction and expectation regarding nursing care provided in selected public and private hospitals in rural areas of Uttara Kannada district, Karnataka, India- A comparative study - P M, Harish; D’souza, Verginia; Satheesan, Aiswarya; George, Aleena; Mary Kurian, Anila; ES, Anisha; Mary Kurian, Anitta; Thomas, Anse; Sebastian, Ashly; D, Aziinai; Noronha, Babitha; June Clara Kharumnuid, Cherrie (International Journal of Nursing Research, 2023)
Nursing service is one of the most important components of hospital service. High level of satisfaction and expectation with nursing care services is the main key to the success of hospitals. Aim: This study is aimed to compare the patient satisfaction and expectation regarding nursing care provided in selected public and private hospitals in rural areas of Uttar Kannada. Method: A Total of 100 patients (50 samples from each Public and Private Hospitals) were selected from public and private hospitals by using the purposive sampling technique. Data were collected by using the Likert scale on satisfaction and Expectation checklist of nursing care. Result: The data revealed that mean patient satisfaction regarding nursing care in private Hospital was 77.89 and in public hospital 75.02 and there is no significant difference (t=1.79 <,t98=1.98 at the p≤0.05 level of significance) between the Patient Satisfaction regarding Nursing care provided in selected Private and Public hospital. The mean patient expectation regarding nursing care was found 13.71 in private Hospital and 15.32 in public Hospitals and there is significant difference ( t=3.09> t98=1.98 at the p≤0.05 level of significance) between the patient Expectation regarding nursing care provided in selected Private and Public hospital. Data revealed that there is a significant association between the Gender, Religion and the History of the Previous Hospitalization with the level of Satisfaction and there is a significant association between the marital status and patient expectation with nursing care. Conclusion: The study concluded that Vagarious and systematic staff development, in service and training programs can be conducted to improve patient care